Upaya Guru PAI Dalam Meningkatkan Kemampuan Belajar Baca Al – Qur’an Melalui Metode Tilawati di SDIT Uswatun Hasanah Depok - Firman Maulana; Fahmi Irfani (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2022)
With the PAI learning to read the Koran using the classical method, students experience learning saturation, so that students' willingness to learn decreases during the PAI learning process to read the Koran. Therefore, Islamic religious education teachers should strive to redevelop learning methods and students' interest in learning during PAI learning in reading the Koran. The purpose of this study is to analyze the efforts and constraints of PAI teachers in using PAI learning methods. The method in this study uses a case study research approach, which is a method for collecting and analyzing data on a particular case. The results of this study are the various efforts of Islamic religious education teachers in developing interest in learning to read the Al-Quran in PAI lessons including: recognizing hijaiiyah letters, motivating students, holding Al-Quran reading tests one by one, directing parents and guardians of students to provide stimulus children in learning to read the Koran, and teaching reading the Koran at home. And there are several obstacles faced by PAI teachers during the implementation of learning to read the Al-Quran: students do not know the hijaiyyah letters, it is still difficult to pronounce Arabic letters, students do not recite the Koran at home, students experience lack of fluency in reading the Koran, and lack of attention and attention. directions from parents. Keywords: PAI teacher; Learning Ability; tilawati method